MECANISMO DE AUXÍLIO AO PROFESSOR PARA O AMBIENTE NETCLASS DE ENSINO-APRENDIZAGEM. - BRANDÃO NETO, PEDRO (2007)
Distance Education environments, nowadays, provide means for learner evaluation. This task, still, requires effort of the teacher. So, the learner accompaniment in distance teaching-learning environments, obtained through the observation of the learner activities, it presents referring problems to the lack of mechanisms that offer an effective support to the teacher in the orientation for the learner. These existent mechanisms only present results to the teacher without to do any inference, like this, self teacher needs to analyze those results manually in search of subsidies to do a precise orientation, showing the possible causes and addressing the learner for the correct road. However, to dower a mechanism with inference capacity is necessary to capture the knowledge of as the teacher fulfills the leaner accompaniment for, later, to transfer this knowledge for a knowledge base with inference capacity. The necessary knowledge for the teacher to realize the learner accompaniment in a teaching-learning environment is the evaluation criterions that are defined by course pedagogic coordination or teacher of the teaching institution. However, those evaluation criterions are generic and not standardized hindering, therefore, the consent of the same; was realized a theoretical rising for the definition of the evaluation criterions in the NetClass environment. This research generated the knowledge on the development of a model denominated Learner Accompaniment Support Mechanism based on techniques of Artificial Intelligence, which is applied to the NetClass environment of teaching-learning.